2004
DOI: 10.1182/blood-2003-02-0438
|View full text |Cite
|
Sign up to set email alerts
|

The impact of donor KIR and patient HLA-C genotypes on outcome following HLA-identical sibling hematopoietic stem cell transplantation for myeloid leukemia

Abstract: Killer immunoglobulin-like receptors (KIRs) regulate cell activity of natural killer (NK) cells and some T cells. The predominant ligand for inhibitory KIRs is HLA-C, which subdivides into 2 groups based on the specificity of inhibitory KIRs. The ligands for activatory KIRs are unknown. Following hematopoietic stem cell transplantation (HSCT), recipient tissues may not express a ligand for KIRs present within the graft, and the combination of donor KIR and recipient HLA-C types could influence outcome. HLA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
5
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(161 citation statements)
references
References 37 publications
(45 reference statements)
9
142
5
4
Order By: Relevance
“…Whereas in one study, C2 ligands were associated with an increased relapse rate (22), in another study epistatic interaction between C2 in the recipient and the stimulatory KIR2DS2 in the donor was found (23). In the present study, no influence of C2 ligands on the relapse rate was found.…”
Section: Discussioncontrasting
confidence: 73%
“…Whereas in one study, C2 ligands were associated with an increased relapse rate (22), in another study epistatic interaction between C2 in the recipient and the stimulatory KIR2DS2 in the donor was found (23). In the present study, no influence of C2 ligands on the relapse rate was found.…”
Section: Discussioncontrasting
confidence: 73%
“…13 Also, the analyses of the activating KIR receptors showed donors' KIR2DS2 to be a significant risk factor for overall survival (OS) of myeloid leukemia HLA-C2C2 patients. 14 In addition, not only individual genes but also KIR haplotypes of donors were associated with an increased risk of acute GVHD (aGVHD), higher relapse rates and worse OS of HLA-C1C1 patients diagnosed with myeloid diseases. 15 However, all described observations apply to distinct patient groups, and differ substantially depending on transplant protocols, as reviewed recently by Verheyden and Demanet.…”
Section: Introductionmentioning
confidence: 99%
“…12 Subsequently, a second model known as the receptorligand model (or missing ligand model) was proposed, in which the consideration is on the KIR genotype rather than the ligand of the donor's KIR and whether its corresponding ligand is missing in the recipient. There are several reports retrospectively analyzing transplant outcome on the basis of this model, with some showing an advantage in certain aspects, for example OS, 13,14 relapse-free survival and 13-15 TRM, 13,16 whereas others failed to find any beneficial effects. These discrepancies are probably linked to heterogeneous patient populations, differences in the sources of stem cells and various conditioning regimens.…”
Section: Introductionmentioning
confidence: 99%